Post-EMR for colorectal polyps, thermal ablation of defects reduces adenoma recurrence: A meta-analysis - Kandel, Pujan; Hussain, Murtaza; Yadav, Deepesh; Dhungana, Santosh K.; Brahmbhatt, Bhaumik; Raimondo, Massimo; Lukens, Frank J.; Bachuwa, Ghassan; Wallace, Michael B. (Endoscopy International Open, 2022)
Background and study aims Adenoma recurrence is one of the key limitations of endoscopic mucosal resection (EMR), which occurs in 15 % to 30 % of cases during first surveillance colonoscopy. The main hypothesis behind adenoma recurrence is leftover micro-adenomas at the margins of post-EMR defects. In this systematic review and meta-analysis, we evaluated the efficacy of snare tip soft coagulation (STSC) at the margins of mucosal defects to reduce adenoma recurrence and bleeding complications.Methods Electronic databases such as PubMed and the Cochrane library were used for systematic literature search. Studies with polyps only resected by piecemeal EMR and active treatment: with STSC, comparator: non-STSC were included. A random effects model was used to calculate the summary of risk ratio and 95 % confidence intervals. The main outcome of the study was to compare the effect of STSC versus non-STSC with respect to adenoma recurrence at first surveillance colonoscopy after thermal ablation of post-EMR defects.Results Five studies were included in the systematic review and meta-analysis. The total number patients who completed first surveillance colonoscopy (SC1) in the STSC group was 534 and in the non-STSC group was 514. The pooled adenoma recurrence rate was 6 % (37 of 534 cases) in the STSC arm and 22 % (115 of 514 cases) in the non-STSC arm, (odds ratio [OR] 0.26, 95 % confidence interval [CI], 0.16–0.41, P = 0.001). The pooled delayed post-EMR bleeding rate 19 % (67 of 343) in the STSC arm and 22 % (78 of 341) in the non-STSC arm (OR 0.82, 95 %CI, 0.57–1.18).Conclusions Thermal ablation of post-EMR defects significantly reduces adenoma recurrence at first surveillance colonoscopy.